Revealing the Role of Aggregation and Surface Chemistry in the Bi‐phasic Anion Exchange Reactions of Cesium Lead Halide Perovskites. Issue 13 (2nd April 2020) - Sandeep, K.
Abstract: Tuning the emission of cesium lead halide perovskites by the post‐synthetic halogen exchange reactions is one of the easiest methods to obtain the opto‐electronic materials having emission in the entire visible region. Role of aggregation and the surface chemistry on the room temperature bi‐phasic anion exchange reactions of CsPbBr3 nanocrystal is investigated. Aggregation of the nanocrystals resulted in the decrease of surface bromide ions and CsPbBr3 became inactive towards the bi‐phasic anion exchange reactions. On the modification of the surface by enriching with bromide ions, aggregated CsPbBr3 nanocrystals became active towards anion exchange reaction. Surface halide ions have a significant role in the anion exchange reactions and the reaction starts at the surface and diffuses to the inner parts of the crystal as a result of its soft crystal nature. Understanding the role of surface chemistry on the anion exchange reactions, the potential of aggregated CsPbBr3 nanocrystals can be used for the opto‐electronic applications. Abstract : Surface Chemistry and aggregation of the CsPbBr3 nanocrystals have a crucial role in the bi‐phasic anion exchange reactions. Upon aggregation, CsPbBr3 nanocrystals become inactive towards anion exchange reactions. By modifying the surface of CsPbBr3 nanocrystals with bromide ions, herein, we could make them active towards anion exchange. In this way, the potential of aggregated CsPbBr3 nanocrystals can be used for various applications.